A comparison of micro-CT and histomorphometry for evaluation of osseointegration of PEO-coated titanium implants in a rat model. Issue 1 (December 2017) - He, Tao; Cao, Cong; Xu, Zhiguo; Li, Gen; Cao, Huiliang; Liu, Xuanyong; Zhang, Chao; Dong, Yuqi
Abstract The aim of the present study was to determine the correlation between bone volume density (BV/TV) around a titanium implant determined by micro-computed tomography (micro-CT) and bone area density (BA/TA) measurements obtained using histomorphometry. An intramedullary rat femur implant model was evaluated to compare raw titanium implants with plasma electrolytic oxidation (PEO)-coated titanium implants. Titanium and PEO-treated titanium pins were inserted into rat femurs under general anesthesia. The animals were sacrificed and femurs harvested at 0, 2, 4 and 6 weeks, and subsequently, histomorphometry and micro-CT were performed. BV/TV and BA/TA values were strongly and positively correlated at all time points and locations (with all correlation coefficients being >0.8 and with P < 0.001). BV/TV and BA/TA were significantly higher proximal to the growth plate than distal to the growth plate, with estimated differences of 14.10% (P < 0.001) and 11.95% (P < 0.001), respectively. BV/TV and BA/TA were significantly higher on the PEO-coated surface than on the raw titanium surface, with estimated differences of 3.20% (P = 0.044) and 4.10% (P = 0.018), respectively. Therefore, quantitative micro-CT analysis of BV/TV is correlated with BA/TA determined by histomorphometry when artifacts around titanium implants are minimized by a region of interest modification.